What is equitable about equitable resilience? Dynamic risks and subjectivities in Nepal. (November 2022) - Forsyth, Tim; McDermott, Constance L.; Dhakal, Rabindra
Highlights: It is critical to theorize equity in the context of equitable resilience. Predefined visions of equity and transformative change hide contextual and intersectional agencies and experiences of risk. In Jumla, Nepal, state-led interventions define equity as "equal distribution" that do not acknowledge social differences such as caste and gender. Yet, focusing on caste and gender as indicators of marginalization also overlook contextual and dynamic influences on risk. Equitable resilience requires recognizing intersectional inequalities and local agency, not predefined indicators of risk and vulnerability. Abstract: Equitable resilience is an increasing focus of development policy, but there is still insufficient attention to how the framings of equity itself shape what, and who, is targeted through development efforts. Universalistic assumptions about climate risk or social marginalization can define equity in ways that hide dynamic and intersectional influences on what constitutes risk to whom under different circumstances. This paper investigates the implications of two different equity framings for resilience in Jumla District, western Nepal. Drawing on more than one hundred household surveys plus in-depth qualitative interviews in six villages, we find that state-led efforts to present post-civil war development as the "equal distribution" of roads and infrastructure, agricultural commercialization, and protection against systemic climate risk fail to reflect local experiences of risk, which are often expressed in terms of social exclusion rather than vulnerability to climate change. Yet, simultaneously, other efforts at building resilience that use caste and gender as indicators of social marginalization overlook how transitions in livelihoods and individual agency have changed vulnerability contexts for many people, or the increasing vulnerability to climate change of more landed farmers. The paper urges more critical attention to how normative framings of equity shape what, and for whom is considered equitable resilience, including assumptions about transformative change from analysts themselves. Representing risks and vulnerability in terms of socially marginalized groups alone might deny the dynamic, intersectional, and contextual interconnection of risks and social agency; and might impose unhelpful subjectivities of their own.